FINANCIAL DISTRESS, KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI - Hasby Muhammad Syifa; Farida Titik Kristanti; Vaya Juliana Dillak (JRAK, 2017)
Financial report describes the performance of a company. Accounting conservatism makes accountants have to note the possibility of losses as soon as possible and also note the profit when it is realized. This study aims to analyze the effect of financial distress, institutional ownership, and the profitability towards accounting conservatism. The population in this study is the food and beverages companies that listed in IDX (Indonesia Stock Exchange) in 2011-2015. The sampling method used in this research is purposive sampling method, in which the population sample are the companies that publishing its financial reports and annual reports for 5 periods started from 2011 to 2015. In the result, it is obtained a sample of 8 companies with 40 units of observation data. The analysis method of data analysis used is panel of data regression analysis. The results of this study showed that simultaneous variable financial distress, institutional ownership, and profitability have significantly influenced to accounting conservatism. Furthermore, in partial variable, financial distress and profitability have positive impact to accounting conservatism. Meanwhile, institutional ownership variable has no impact to accounting conservatism.